Morphine-induced pruritus after epidural administration followed by treatment with naloxone in a cat - Evangelista, Marina C. [UNESP]; Steagall, Paulo; Garofalo, Natache A. [UNESP]; Rodrigues, Jessica C. [UNESP]; Teixeira-Neto, Francisco [UNESP] (SAGE Publications, 2016)
Case summary A young male domestic shorthair cat weighing 1.6 kg was admitted to a veterinary teaching hospital for elective orchiectomy. A lumbosacral epidural injection of preservative-free morphine (0.1 mg/kg) and lidocaine (0.25 ml/kg) was performed under general anesthesia. One hour after extubation, the cat became agitated. Severe licking and biting of the hindlimbs, tail and lumbar area were observed. Pruritus was suspected and likely to be caused by epidural morphine. Acepromazine (0.02 mg/kg IM) was administered but clinical signs did not cease. Naloxone (2 µg/kg IV) was administered and clinical signs resolved within 20 mins. Relevance and novel information Different therapeutic approaches are available for the treatment of morphine-induced pruritus. This case describes an additional treatment option using opioid antagonism with naloxone.